Affymetrix GeneChip system: moving from research to the clinic. - Ragoussis, J; Elvidge, G (2006)
Affymetrix Inc.'s GeneChip technology has become the industry standard in microarray-based research. Due to the high density of content per array that can be achieved today (an industry leading 6.5 million features) the GeneChips can be used for high-throughput mutation detection, single nucleotide polymorphism genotyping, expression profiling and detection of chromosomal aberrations. This in turn opens the way for clinical applications in genetics, cytogenetics, pharmacogenetics, oncology and pathogen recognition. Establishing standards is a central issue in improving data quality and, in combination with automatic, easy-to-interpret reports, will form the basis of the clinical applicability. Future pricing policies and the resolving of ethical considerations will also dictate the technology's full translation from research into clinical laboratories.